Possibilities of Correction and Prophylaxis of Intestinal Microbiocenosis Disorders in Frequently Ill Children - A. N. Surkov (Вопросы современной педиатрии)
Frequently and protractedly ill children constitute a special for pediatricians group of patients. Acute respiratory infections with severe and frequently relapsing course badly affect children’s health and contribute to the decrease of the functional activity of the immune system. Risk factors of the high prevalence of acute respiratory infections are changes in the immune responses at the background of unfavorable ante- and perinatal conditions, numerous contacts with potential causative agents at the beginning of attendance of infant schools, widespread intra- and inter-family contacts as well as susceptibility to Th2 immune response (allergy) and prolonged course of inflammatory process. Etiotropic treatment of acute respiratory infections often includes antibacterial drugs, which, however, have negative effects on intestinal microflora, such as dyspeptic syndrome and antibiotic-induced diarrhea. Intestinal dysbiosis affects homeostasis, leads to significant changes in functional activity of various organs and systems. That is why correction and prophylaxis of intestinal dysbacteriosis is very important in pediatric practice. In this article the main data on epidemiology, pathogenesis, forms, clinical manifestation, diagnostics and treatment of antibiotic-induced diarrhea in children.